The effect of nano-sized BNBT on microstructure and dielectric/piezoelectric properties - Yoon, Man-Soon; Khansur, Neamul Hayet; Choi, Byung-Ki; Lee, Young-Geun; Ur, Soon-Chul (Ceramics International, 2009)
(Bi(0.5)Na(0.5))(0.94)Ba(0.06)TiO(3) (abbreviated as BNBT6) ceramic of near MPB composition was synthesized by two different processes. The first one is the addition of pre-synthesized BaTiO(3) and pre-milled Bi(2)O(3), Na(2)CO(3), BaCO(3) powders and calcination powder milled with a high energy milling machine in order to obtain a nano-particle size. The second one is a conventional one to compare with the former process. The pre-milling and the pre-synthesis process of raw materials lowered the calcination temperature to the extent of 59 degrees C as compared with conventionally fabricated BNBT6. The particle size of the powder exposed to heavy high energy milling reduced to 50-70 nm, whereas that of the conventionally ball-milled powder without the pre-milling and the pre-synthesis process had a larger size of similar to 280 nm. To investigate the effects of the modified process on the characteristic of BNBT6 ceramics, the dielectric and the piezoelectric properties of sintered specimens fabricated by the two different processes were evaluated. It was found that the properties of the nano-sized BNBT6 ceramic near the MPB composition were increased by the modified mixing and milling method, showing superior characteristics in terms of the piezoelectric/dielectric constant and sintering density compared with those of the conventional process. The modified mixing and milling method was considered to be a new and promising process for lead-free piezoelectric ceramics owing to their excellent piezoelectric/dielectric properties. Crown Copyright (c) 2009 Published by Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Piezoelectric properties; Dielectric properties; Pre-milling; Nano-sized BNBT